A critical assessment of Brazilian manufacturing competitiveness in foreign markets. Issue 3 (15th May 2017) - Cyrino, Alvaro Bruno; Parente, Ronaldo; Dunlap, Denise; de Góes, Bruno B.
Abstract : Purpose: This study aims to examine the competitiveness of firms operating in the emerging economy of Brazil. This study examines the current perception of Brazilian business leaders regarding the level of competitiveness in various sectors of industrial activity and the country's business environment. Design/methodology/approach: Survey data were collected in a joint study developed by Brazilian School of Public and Business Administration (EBAPE) and the Brazilian Institute of Economics (IBRE). The population surveyed was composed of businessmen, managers and directors of Brazilian manufacturing firms. This survey was created based on a similar survey conducted by the Harvard Business School, which was also aimed at identifying the reasons behind national loss of competitiveness. Findings: The results of the survey point out that the worsening competitive nature of companies operating in Brazil can be primarily attributed to the deterioration of its country-specific advantages and in particular those linked to government policies, services and bureaucratic procedures, all of which bear a negative impact on the country's business environment. Research limitations/implications: Future research should explore in more depth the specific types of initiatives that these firms have and are continuing to eagerly adopt with the aim of improving their domestic competitiveness and, namely, firm-specific advantages, whether it be by contributing to the improvement of the business environment as a whole, or by improving their own operations and management systems. Practical implications: The main obstacles related to competitiveness are associated with the "Brazil Cost", namely, the tax system, infrastructure, political system, labor laws and bureaucracy that do not appear to offer much room for maneuvering in terms of reducing these barriers in the short term. Managers not addressing these important input factors of competitiveness not only divert attention away from innovation and creativity but also could lead to more serious political, social welfare and economic implications in the global marketplace. Social implications: This study helps to gain a better understanding of the initiatives that could and are being used to contribute to a fruitful discussion about leading public policies and government actions geared toward upgrading Brazil's business environment and country competitiveness as a whole. Originality/value: This research contributes to the understanding of the initiatives that could and are being used to improve firm competitiveness in Brazil. These initiatives contribute to a fruitful discussion about leading public policies and government actions geared toward upgrading Brazil's business environment and country competitiveness as a whole.